A randomised exploratory clinical evaluation of dentifrices used as controls in dentinal hypersensitivity studies. (September 2017) - Gallob, John; Sufi, Farzana; Amini, Pejmon; Siddiqi, Muhammad; Mason, Stephen
Abstract: Objectives: To explore relative efficacy of six negative-control dentifrices utilised as controls in clinical studies compared with two dentine hypersensitivity (DH)-relief dentifrices used 2×/day for 8 weeks. Methods: Six control dentifrices differing in terms of fluoride source (sodium fluoride/sodium monofluorophosphate), abrasive base (silica/dicalcium phosphate), relative dentine abrasivity (RDA) (∼17 to ∼180) and colour (white/blue/multicoloured stripes) were compared with a depolarising dentifrice (5% KNO3 ; RDA ∼70–97; 'Test 1') and an occlusion-technology dentifrice (0.454% SnF2 ; RDA ∼160–180; 'Test 2'). DH was assessed using tactile and evaporative (air) (measured by Schiff Sensitivity Scale and a visual rating scale [VRS]) stimuli. Results: In total 249 subjects were randomized. All dentifrices yielded statistically significant improvements from baseline on all endpoints. The two DH-relief dentifrices ranked highest in terms of improvement in scores over the control dentifrices. While there was a clear differentiation between Test 1 and control dentifrices on both measures at 4/8 weeks, for Test 2, statistically significant improvements in Schiff scores were observed over all controls at Week 4 but only over three at Week 8. At Week 4 none of the controls separated from Test 2 on tactile threshold; all separated by Week 8. VRS scores did not separate test and control dentifrices. Dentifrices were generally well-tolerated. Conclusions: The six negative-control dentifrices can be used to assess dentifrices considered to be effective in reducing DH. Although response ranges for commercially available negative controls varied, these results may begin to set acceptable performance ranges for control dentifrices in DH trials.